2015
DOI: 10.1002/dmrr.2648
|View full text |Cite
|
Sign up to set email alerts
|

Solving the mystery: the true prevalence of gestational diabetes in indigenous women

Abstract: This commentary briefly reviews what is currently known about estimating the prevalence of gestational diabetes in indigenous women. It offers insights into numerous factors likely playing a role in its observed variability. It also highlights important key concepts to consider in the overall evaluation and management of gestational diabetes in this particular population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…First Nation ethnicity is an independent predictor for GDM [48]. As noted by Saad, Wilson and Donovan [59], research has not sufficiently evaluated the role of socioeconomic status, a key risk factor for obesity and GDM among Indigenous women [59,[68][69][70][71], and future research should further investigate this critical relationship. Of specific concern noted in the literature is the increased risk of developing T2DM after GDM for both mother [4,34,52,[72][73][74][75] and child [76,77].…”
Section: Gestational Diabetes Mellitus and Intergenerational Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…First Nation ethnicity is an independent predictor for GDM [48]. As noted by Saad, Wilson and Donovan [59], research has not sufficiently evaluated the role of socioeconomic status, a key risk factor for obesity and GDM among Indigenous women [59,[68][69][70][71], and future research should further investigate this critical relationship. Of specific concern noted in the literature is the increased risk of developing T2DM after GDM for both mother [4,34,52,[72][73][74][75] and child [76,77].…”
Section: Gestational Diabetes Mellitus and Intergenerational Riskmentioning
confidence: 99%
“…Chamberlain et al's systematic review [52] reported GDM prevalence rates for Australian Indigenous females ranging from 1.33% to 18.51%, while prevalence rates of GDM in Canada's First Nations population reported 3 times higher than the non-First Nations population [47,51]. GDM screening is important for capturing accurate prevalence rates, and limited/inconsistent screening practices and inconsistent study designs helps to explain the varying rates of GDM noted in the literature [57][58][59]. In Cape York, Australia, a three-fold increase in GDM was observed over a two year period with the introduction of universal screening [58].…”
Section: Gestational Diabetes Mellitus and Intergenerational Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Most experts agree that a focus on “ethnicity as a proxy for genetic variation” being a primary determinant of GDM risk diverts attention away from the wider determinants affecting Indigenous peoples’ health [ 30 ]. In fact, the contribution of socioeconomic and psychosocial deprivation to GDM prevalence among Indigenous women has not been adequately evaluated [ 31 ]. The experience of “unequal treatment” [ 29 ] for Indigenous women with GDM also receives little attention, despite several small studies and a recent audit reporting inequities in screening, diagnosis and management of GDM between Māori and non-Māori [ 22 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%